“Everything has its Limits!” The Berlin Wall and the Problem of Desire (Konturen, 2013)
By the East German authorities’ account, the “Anti-Fascist Wall of Protection,” or Berlin Wall, was built to thwart hordes of anti-communist commandos poised to invade the socialist republic. If the Party acknowledged the stream of refugees from East to West at all, it was only to decry the efforts of paid agitators luring or coercing skilled East German workers over the border. These paranoid scenarios, I will argue, represented more than just hard-line propaganda and political expediency; they arose from fundamental assumptions about the psyche and society. Through an exploration of East German cultural responses to the construction of the Wall, my paper outlines the ideological fantasies of the individual and social body that precipitated this drastic measure.